2013
DOI: 10.1007/s00240-013-0565-8
|View full text |Cite
|
Sign up to set email alerts
|

Tubeless procedure reduces hospitalization and pain after percutaneous nephrolithotomy: results of a multivariable analysis

Abstract: The objective of the study was to assess the efficacy and safety of tubeless percutaneous nephrolithotomy (t-PCNL) in comparison with standard PCNL (s-PCNL). We retrospectively evaluated 317 consecutive PCNL and compared perioperative results, time of hospitalization and analgesic requirement of t-PCNL (114; 36.0 %) to s-PCNL (203; 64.0 %). The decision to perform a tubeless PCNL was made at the end of the procedures depending on the surgeon's preference and according to the following inclusion criteria: (a) n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
1
16
1
Order By: Relevance
“…16 In our study, we performed tubeless PCNL in 17 patients. Of these patients, 4 had a double-J stent insertion, 7 a ureteral catheter insertaion and the remaining 6 were totally tubeless.…”
Section: Discussionmentioning
confidence: 99%
“…16 In our study, we performed tubeless PCNL in 17 patients. Of these patients, 4 had a double-J stent insertion, 7 a ureteral catheter insertaion and the remaining 6 were totally tubeless.…”
Section: Discussionmentioning
confidence: 99%
“…15 There have been significant advances in the percutaneous extraction of renal calculi. [2][3][4][5][6][7][8][9][10] Review articles have highlighted the need for minimal intra-operative bleeding, negligible residual stone burden, and one to two attempts at renal access when considering tubeless approaches. Recently, the ability to perform tubeless PCNL as an outpatient procedure has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Tubeless PCNL, with ureteral stenting, has been shown to decrease patients' analgesic requirements and hospital length of stay. 9,10 Although hospitalization is standard practice after PCNL, reports have described success with outpatient management. 11,12 This case report is the first to describe successful outpatient PCNL in a renal transplant patient.…”
Section: Introductionmentioning
confidence: 99%
“…3 Numerous studies have supported the use of the tubeless method as a viable alternative to standard PCNL. 1,[4][5][6][7] The advantages of tubeless PCNL over the standard procedure include reduced postoperative analgesic requirements, as well as reduced duration of hospitalization without an increase the rate of complications. Surgical advancements have enabled the use of tubeless PCNL in complex cases, including pediatric, geriatric and bilateral simultaneous renal calculi.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies to date have demonstrated that this is a safe and effective method of stone burden clearance in select patients. 1,[3][4][5][6][7] Recently, tubeless PCNL, on an outpatient basis, has been reported. 8,9 This case report is the first to describe a case of outpatient bilateral tubeless PCNL in a patient with bilateral large staghorn calculi.…”
Section: Introductionmentioning
confidence: 99%